KEMAMPUAN BERPIKIR KRITIS - KOWIYAH, KOWIYAH (JURNAL PENDIDIKAN DASAR, 2012)
Ability thinks critical is an cognitive activity or process and action of mental to obtain knowledge, understanding and skill in a hope that is able to find way out and performs decision deductively, inductive and evaluatif as according to its step which is performed with thinking exhaustively about things which can be reached by experience of someone, inspection and performs logical common sense which is measured by through interpretation efficiency, analysis, assumptions recognition, deduction, evaluation inference, eksplanasi / explanation of, and xâself regulation.Key word: Ability, Think, Analysis, Critical